BOOK REVIEWS (Journal of Finance, 1976)
Book reviewed in this article: Issues in Monetary Economics , (Proceedings of the 1972 Money Study Group Conference). H. G. J ohnson and A. R. N obay Monetary Economics . By D. G. P ierce and D. M. S haw The Bankers . By M artin M ayer Security Analysis and Portfolio Management . By D onald E. F ischer and R onald J. J ordon Financial Ratios and Investment Results By D onald M. P eterson The Strategy of Cash . By S. D. S later Finance as a Dynamic Process . By E dwin J. E lton and M artin J. G ruber Property Taxation and the Finance of Education . Edited by R ichard W. L indholm Real Estate and Urban Land Analysis . Edited by J ames R. C ooper and K arl L. G undermann Methods and Techniques of Business Forecasting . Edited by W illiam F. B utler , R obert A. K avesh , and R obert B. P latt The Effect of Social Security on Personal Saving . By A licia H aydock M unnell